FRI0447 Long-Term (156-Week) Efficacy and Safety Profile of Apremilast, An Oral Phosphodiesterase 4 Inhibitor, in Patients with Psoriatic Arthritis: Results from A Phase III, Randomized, Controlled Trial and Open-Label Extension (Palace 1). (15th July 2016) - Kavanaugh, A.; Gladman, D.D.; Gomez-Reino, J.J.; Hall, S.; Lespessailles, E.; Mease, P.J.; Schett, G.; McIlraith, M.; Shah, K.; Teng, L.; Wollenhaupt, J.
Abstract : Background: Long-term data on the efficacy and safety of therapies is vital for treatment decision making in chronic diseases such as psoriatic arthritis (PsA). Three-year treatment data from the PALACE 1 (NCT01172938 ) study of apremilast (APR) in patients with active PsA despite previous conventional disease-modifying antirheumatic drug (DMARD) or biologic therapy has recently become available. Objectives: Using data from 3 years of treatment, examine the longer term efficacy/safety of APR. Methods: Patients were randomized (1:1:1) to placebo (PBO), APR 30 mg BID (APR30), or APR 20 mg BID (APR20) stratified by baseline DMARD use (yes/no). The PBO-controlled phase continued to Wk 24, with an early escape option at Wk 16. At Wk 24, all remaining PBO patients were re-randomized to APR30 or APR20. Double-blind APR treatment continued to Wk 52; patients could continue APR for up to 4 additional years. Efficacy assessments in years 2 and 3 were conducted at Wks 65, 78, 91, 104, 117, 130, 143, and 156. Results: 504 randomized patients received ≥1 dose of study medication (PBO: n=168; APR30: n=168; APR20: n=168). In an "as observed" analysis, 53.2% (APR30) and 59.6% (APR20) of patients achieved a modified ACR20 response at Wk 52 (Table ), regardless of when APR was started (baseline, Wk 16, or Wk 24). Of the patients entering year 2, 65.3% (APR30) and 60.9% (APR20) attained these responses at Wk 104. A total of 92% (260/284) of the patients starting the third year of the trial completed the Wk 156 visit; overall, this is 52% (260/504) of patients randomized at baseline. Patients receiving APR30 at Wk 156 demonstrated sustained improvements, as shown by ACR20 response rates of 65%, swollen/tender joint count mean percent improvements of -81.2% and 73.2%, and HAQ-DI mean change of -0.37, and 41.9% of patients reaching DAS (CRP) <2.6. Similarly, the proportion of patients with HAQ-DI exceeding the minimal clinically important difference (MCID) ≥0.30 threshold, mean change in DAS-28 (CRP), and PASI-75/PASI-50 responses were maintained (Table ). No new safety concerns were identified with up to 156 wks of APR treatment. During Wks >104 to ≤156 of APR exposure, the only adverse event (AE) occurring in ≥5% of patients was upper respiratory tract infection; most AEs were mild/moderate in severity. Serious AEs occurred in 6.9% (APR30) and 6.4% (APR20) of patients, similar to rates seen for the earlier study periods, few discontinuations due to AEs (0.7%) occurred over Wks >104 to ≤156. Conclusions: Over 156 wks, among patients remaining in the study, APR demonstrated sustained and clinically meaningful improvements in PsA signs/symptoms, including physical function and associated psoriasis. APR continued to demonstrate an acceptable safety profile and was generally well tolerated. Acknowledgement: We thank Adewale O. Adebajo for his work on the original abstract. Disclosure of Interest: A. Kavanaugh Grant/research support from: Abbott, Amgen, Astra-Zeneca, Bristol-Myers Squibb, Celgene Corporation, Centocor-Janssen, Pfizer, Roche, UCB, Consultant for: Abbott, Amgen, Astra-Zeneca, Bristol-Myers Squibb, Celgene Corporation, Centocor-Janssen, Pfizer, Roche, UCB, D. Gladman Grant/research support from: AbbVie, Amgen, Bristol-Myers Squibb, Celgene Corporation, Janssen, Pfizer, Novartis, UCB, Consultant for: AbbVie, Amgen, Bristol-Myers Squibb, Celgene Corporation, Janssen, Pfizer, Novartis, UCB, J. Gomez-Reino Grant/research support from: Roche, Schering-Plough, Consultant for: Bristol-Myers Squibb, Pfizer Inc, Roche, Schering-Plough, UCB, Speakers bureau: Bristol-Myers Squibb, Roche, Schering-Plough, Wyeth, S. Hall Grant/research support from: Celgene Corporation, Pfizer, UCB, Bristol-Myers Squibb, Glaxo-Smith Kline, Roche, Janssen, Novartis, Merck, Consultant for: Celgene Corporation, Pfizer, UCB, Bristol-Myers Squibb, Glaxo-Smith Kline, Roche, Janssen, Novartis, Merck, E. Lespessailles Grant/research support from: Amgen, Eli Lilly, Novartis, Servier, Speakers bureau: Amgen, Eli Lilly, Novartis, Servier, P. Mease Grant/research support from: Abbott, Amgen, Biogen Idec, Bristol-Myers Squibb, Genentech, Janssen, Eli Lilly, Pfizer, Celgene Corporation, Novartis, Roche, Consultant for: Abbott, Amgen, Biogen Idec, Bristol-Myers Squibb, Genentech, Janssen, Eli Lilly, Pfizer, Celgene Corporation, Novartis, Roche, Speakers bureau: Abbott, Amgen, Biogen Idec, Bristol-Myers Squibb, Genentech, Janssen, Eli Lilly, Pfizer, G. Schett Grant/research support from: Abbott, Celgene Corporation, Roche, UCB, Consultant for: Abbott, Celgene Corporation, Roche, UCB, M. McIlraith Employee of: Celgene Corporation, K. Shah Employee of: Celgene Corporation, L. Teng Employee of: Celgene Corporation, J. Wollenhaupt Grant/research support from: Abbott, Bristol-Myers Squibb, MSD, Pfizer, UCB, Consultant for: Abbott, Bristol-Myers Squibb, MSD, Pfizer, UCB